FEATURES OF THE QUALITY ASSURANCE PROCESS OF HIGHER EDUCATION IN ARMENIA AND ITALY: COMPARATIVE ANALYSIS (EDUCATION IN THE 21ST CENTURY, 2024)
The purpose of the article is to analyze the specific features of the quality assurance process in the higher education systems of Armenia and Italy, identifying the similarities and differences.The quality assurance framework for higher professional education in both Armenia and Italy is based on the principles of quality assurance of the European Higher Education Area, and each country has clearly defined different processes that cover the entire quality assurance framework.One of the most important achievements in the framework of higher education reforms is the new approach to the quality assurance process, when the quality assurance mechanisms of education were reviewed and introduced in both countries in accordance with the standards in force in the European Higher Education Area.Within the framework of reforms in the field of higher education in Armenia and Italy, appropriate quality assurance and control structures have been formed, contributing to the continuous improvement of the quality of higher education with clearly defined functions.The article examines and presents the standards established in both countries, as well as similarities and differences.
Keywords: Higher education system of Armenia,; higher education system of Italy; higher education,; quality of education